2022
DOI: 10.53730/ijhs.v6ns9.13006
|View full text |Cite
|
Sign up to set email alerts
|

Frequency distribution of hepatitis B virus (HBV) genotypes in Iraqi patients

Abstract: Infection with the hepatitis B virus can lead to asymptomatic carrier status, developing into severe chronic hepatitis, cirrhosis, and hepatocellular carcinoma. Ten genotypes (A-J) and 46 sub-genotypes have been discovered. As a result, the current study was conducted to determine HBV genotypes in Iraqi patients. RT-PCR was used to determine the highest viral load in infected subjects and then used for screening HBV genotyping. The results showed that HBV genotype distribution among HBV infected patients was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Numerous investigations have demonstrated that there is no meaningful correlation between HBV genomes and clinical characteristics such as liver histology, ALT levels, liver fibrosis, and HBeAg status [ 66 , 67 ]. Nonetheless, some research has indicated that a greater viral load may be linked to specific HBV genotypes [ 68 ]. Furthermore, a study discovered that HBV genotypes can affect the longitudinal HBsAg serodecline and the extent of HBsAg seroclearance, indicating a potential interaction between HBV genotype and HLA variations [ 69 ].…”
Section: Prognostic Markersmentioning
confidence: 99%
“…Numerous investigations have demonstrated that there is no meaningful correlation between HBV genomes and clinical characteristics such as liver histology, ALT levels, liver fibrosis, and HBeAg status [ 66 , 67 ]. Nonetheless, some research has indicated that a greater viral load may be linked to specific HBV genotypes [ 68 ]. Furthermore, a study discovered that HBV genotypes can affect the longitudinal HBsAg serodecline and the extent of HBsAg seroclearance, indicating a potential interaction between HBV genotype and HLA variations [ 69 ].…”
Section: Prognostic Markersmentioning
confidence: 99%
“…In the context of microbial infections, the production of IgM serves as the initial defense, followed by the development of IgG for long-term immunity and immunological memory [17]. IgM and IgG antibodies have been detected in patient blood samples within three to six days and eight days following SARS infection [21][22][23]. Therefore, the presence of these antibodies aids in estimating the infection date.…”
Section: Introductionmentioning
confidence: 99%
“…Also, occult hepatitis B virus infection (OBI) is another form of CHB and is estimated to affect 0.82% of the general population around the world (10). The prevalence of HBV in Iraq is 2 -5% in the general population (11), with slight differences in different provinces of the country (11,12).…”
Section: Introductionmentioning
confidence: 99%